2014
DOI: 10.1007/s00415-013-7231-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol levels and the severity and outcomes of acute stroke: a systematic review

Abstract: Studies in non-stroke patients have shown an association between dysregulation of the hypothalamic-pituitary-adrenal axis and morbidity and mortality. We conducted a systematic review to evaluate cortisol levels in acute stroke and their associations with outcome. We searched MEDLINE and EMBASE for articles up to April 2013 and PsychINFO for articles up to July 2013, using the keywords "cortisol" and "stroke" and associated terms or synonyms. We included studies published in peer-reviewed journals that recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 66 publications
(124 reference statements)
4
80
0
1
Order By: Relevance
“…Reports by Katan and Bustamante came to the same conclusion as in our meta-analysis [46,47]. A review by Barugh found that cortisol levels should be linked to the patient dependency, morbidity and mortality but they emphasized that it is not clear whether cortisol relates to these outcomes or relates to the initial stroke severity [48]. Cortisol is a stress-related hormone, and may reflect the degree of severity of the cerebral insult and hence the neurological outcome.…”
Section: Discussionsupporting
confidence: 64%
“…Reports by Katan and Bustamante came to the same conclusion as in our meta-analysis [46,47]. A review by Barugh found that cortisol levels should be linked to the patient dependency, morbidity and mortality but they emphasized that it is not clear whether cortisol relates to these outcomes or relates to the initial stroke severity [48]. Cortisol is a stress-related hormone, and may reflect the degree of severity of the cerebral insult and hence the neurological outcome.…”
Section: Discussionsupporting
confidence: 64%
“…Especially in ischemic stroke patients, day‐long duration of hyperglycemia had a strong association with higher risk of the outcome in the hours after acute stroke, accelerating brain damage 22. Elevation of blood glucose levels caused activation of the coagulant system, suppression of the fibrinolytic system, and production of free radicals 26, 28, 29, 30, 31. This elevation may also lead to acidosis, excitatory amino acids, and injury to the blood–brain barrier, which cause ischemic brain damage in animal models and expand ischemic lesions volumetrically 1, 23, 25, 32.…”
Section: Discussionmentioning
confidence: 99%
“…donia and depression in patients with cerebral infarction which express the relation between cortisol level and some of psychological symptoms [11,23]. Despite numerous studies in this field, disagreements on the effect of cortisol on the prognosis of stroke remain strong so that a systematic review which was published in 2014 showed that elevated cortisol after stroke is associated with dependency, morbidity, and mortality but, there is insufficient evidence to conclude that these relationships are independent of stroke severity [17]. Whether the increase in cortisol level is merely a result of the infarct severity or an independent factor, is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Despite above-mentioned studies, in a number of researches, no association was found between cortisol level and mortality in ischemic stroke patients [3,15,16]. According to these controversies and lack of a final conclusion [17], this study aimed to evaluate serum cortisol level and its prognostic value in patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 92%